Additional parameters to improve the prognostic value of the 8th edition of the UICC classification for human papillomavirus‐related oropharyngeal tumors. Issue 8 (17th May 2022) - Straetmans, Jos M. J. A. A.; Stuut, Marijn; Lacko, Martin; Hoebers, Frank; Speel, Ernst‐Jan M.; Kremer, Bernd
Abstract: Background: The prognostic reliability of the UICC's TNM classification (8th edition) for human papillomavirus (HPV)‐positive tonsillar squamous cell carcinomas (TSCCs) compared to the 7th edition was explored, and its improvement by using additional anatomical and nonanatomical parameters. Methods: One hundred and ten HPV‐positive and 225 HPV‐negative TSCCs were retrospectively analyzed. Survival was correlated with patient and tumor characteristics (7th and 8th edition UICC TNM classification). Results: In HPV‐positive TSCCs, the 8th edition UICC's TNM classification correlated better with prognosis than the 7th edition. Also, smoking status was a stronger prognosticator of survival than UICC staging. Non‐ or former smokers had a 5‐year overall survival of 95.1% regardless of tumor stage. Furthermore, age (>65 years), cN3, and M1 classification were significant prognostic factors. Conclusion: The prognostic value of the 8th edition UICC's TNM classification improved significantly when compared to the 7th edition. Nonetheless, further improvement is possible by adding nonanatomical factors (smoking, age >65 year) and separating N0‐N2 from N3.